Inflation Targeting in Serbia - Jelena Fabris (Journal of Central Banking Theory and Practice, 2015)
Serbia introduced inflation targeting regime in August 2006. After nine years of its application, conclusions may be drawn on the (un)successfulness of the regime. Inflation targets have not been achieved during seven of nine observed years. Key difficulties in the application of the regime refer to insufficient efficiency of monetary policy instruments, insufficient confidence in the domestic currency (widely spread informal euroisation), and indexing of prices according to the exchange rate. The paper consists of four sections. The first section analyses theoretical assumptions of the inflation targeting regime. The second part describes the characteristics of the regime in Serbia. The third section analyses results, while the fourth section analyses the reasons for insufficient efficiency of the regime and gives actual suggestions for improving the existing regime.
Keywords: E31; E42; 330; Serbia; monetary policy; inflation targeting